Studi Sifat Mekanik Komposit Polimer Serat Bambu Dengan Struktur Berlapis - Aminur Aminur; Sudarsono Sudarsono; Raden Rinova Sisworo; Prinob Aksar; Citra Yurnidar Syah; Wa Ode Nartin Hamundu (Politeknik Negeri Ujung Pandang, 2023)
Natural composites are one of the smart materials that have the opportunity to replace the use of synthetic composites. and metal materials. Layered structural composites provide nearly uniform properties on all sides. The purpose of this study was to determine the mechanical properties of tensile, compressive and impact on the behavior of bamboo fiber polymer composites with a layered structure. This research method is experimental where the specimens are made in 2 quasine isotropic configuration configurations namely [+60/0/-60] and [+45/0/-45] with layer thicknesses of 1.0 mm, 1.5 mm, respectively. and 2.0mm. The highest tensile strength is 8.173 N/mm2 in the [+60/0/-60] arrangement and the lowest is 6.196 N/mm2 in the [+45/0/-45] arrangement. The highest impact strength is 34.259 kJ/mm2 in the [+45/0/-45] array configuration and the lowest tensile strength is 10.775 kJ/mm2 in the [+60/0/-60] array configuration. The highest compressive strength is 15.856 N/mm2 in the configuration [+60/0/-60] arrangement and the lowest compressive strength is N/mm2 in the configuration [+45/0/-45]. The [+60/0/-60] array configuration has better mechanical properties than the [+45/0/-45] configuration. Where the tensile strength, compressive strength and impact strength increase with increasing layer thickness.Â Keywords: composite, layered structure, tensile, compressive and impact